Analysis of the hidden-charm-hidden-strange tetraquark mass spectrum via the QCD sum rules - Zhi-Gang Wang (Nuclear Physics B, 2024)
In the present work, we construct the diquark-antidiquark type four-quark currents to investigate the mass spectrum of the ground state hidden-charm-hidden-strange tetraquark states with the quantum numbers JPC=0++, 1+−, 1++ and 2++ via the traditional QCD sum rules in a comprehensive way. We update old calculations, perform new calculations and analysis in a rigorous way, and take account of the net light-flavor SU(3) breaking effects in a consistent way. And we make more reasonable identifications for the X(3960), X(4140), X(4274), X(4500), X(4685) and X(4700) and supersede some old identifications. Furthermore, we consider our previous theoretical predictions, and make reasonable/suitable identifications of the new LHCb states hc(4000) and χc1(4010).